FAKTOR-FAKTOR KENDALA PENGELOLAAN KELAS PADA MATA PELAJARAN TEORI DI SMKN JURUSAN TEKNIK BANGUNAN TAHUN AJARAN 2011/2012 - Ema Sonia Amelinda; Tuti Iriani; Amos Neolaka (LPPM Universitas Negeri Jakarta, 2012)
This research aims to determine the constraint factors affecting the class management of courses content theory in Vocational High School Majoring in Building Construction for the students of Building Construction Education Study Program State University of Jakarta who attend the Teaching Apprenticeship Program (PPL). This research placed in eight vocational schools majoring in Building Construction in March until May 2012. The method used in this research is surveying method. The population in this research is 30 students of Building Construction Education Study Program Department of Civil Engineering Faculty of Engineering State University of Jakarta who teach the class content theory during the PPL. The number of samples is 28 students who are determined using simple random sampling. The additional data to strengthen this research is gained from 75 students (from 3 classes) which are established using purposive sampling. The instrument used in this research is using questionnaire to collect the data about constraint factors affecting the class management to the PPL students. Based on the calculation, we get the value of reliability r is 0.97 for the questionnaire spread both for the students and teachers in vocational high school.Based on the answers of the respondent from the PPL teachers and students, we can see that the students have more honest answer regarding the questionnaire. Constraint factors affecting the class management from the student’s answers to the teacher’s attitude indicator has the average value of 3.32. Constraint factors affecting the class management from the student’s answers to the student’s indicator has the average value of 3.04. Constraint factors affecting the class management from the student’s answers to the classroom management and teaching visual aids indicator has the average value of 2.96. And constraint factors affecting the class management from the student’s answers to the class discipline indicator has the average value of 2.59. Based on this research we can conclude that teacher’s attitude taken into first place for the constraint factors affecting the class management shown by the highest average score 3.32. It is caused by a minimum practice of teaching to the PPL students especially about class management and an ineffectiveness of briefing before PPL